Qaá¸ÄyÄ MahÄrah al-QirÄâ€™ah li á¹¬ullÄb Maâ€™had SÄ«mÄá¹arkÄ«s bi BÄsÄmÄn al-Sharqiyah, DirÄsah Taá¸¥lÄ«l Akhá¹Äâ€™ fÄ« Nuá¹q al-á¸¤urÅ«f al-Hijaâ€™iyah - Handayani, Rika Fitri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The purpose of this study was to analyze the pronunciation errors of the alphabet in the reading skills of the ninth clash students of the SimaÈ›arkis Islamic school in eastern Pasaman. The method used in this study is the method of data collection using the qualitative descriptive analytical approach. The results of this study are that the errors of pronunciation of the alphabet in the reading skill of the students of the Islamic school of SimaÈ›arkis in East Pasaman for the primary stage, the researcher found twenty letters of pronunciation errors, including the pronunciation of the letterÂ ofÂ hÄâ€™, â€˜ayn, á¸¥Äâ€™, ghayn, khÄâ€™, kÄf, qÄf, á¸Äd, jÄ«m, shÄ«n, rÄâ€™,Â á¹Äâ€™, dÄl, tÄâ€™, È˜Äd, zÄy, áº’Äâ€™, dhÄl, thÄâ€™, fÄâ€™. One of the reasons for errors in the pronunciation of the alphabet is that the reading skill of students of the SimaÈ›arkis Islamic school in east Pasaman for the primary stage is linguistic and non-linguistic errors.Ù…Ù† Â Ø£ØºØ±Ø§Ø¶ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù‡Ùˆ ØªØÙ„ÙŠÙ„ Ø£Ø®Ø·Ø§Ø¡ Ù†Ø·Ù‚ Ø§Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ù‡Ø¬Ø§Ø¦ÙŠØ© ÙÙŠ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ù„Ø·Ù„Ø§Ø¨ Ù…Ø¹Ù‡Ø¯ Ø³ÙŠÙ…Ø§Ø·Ø±ÙƒÙŠØ³ Ø§Ù„ØµÙ Ø§Ù„ØªØ§Ø³Ø¹ Ù Ø¨Ø¨Ø§Ø³Ø§Ù…Ø§Ù† Ø§Ù„Ø´Ø±Ù‚ÙŠØ©. ÙˆØ§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…Ø³ØªØ®Ø¯Ù…Ø© ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù‡ÙŠ Ø·Ø±ÙŠÙ‚Ø© Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„Ù†ÙˆØ¹ÙŠ Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠ. ÙˆÙ†ØªØ§Ø¦Ø¬ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ù‡ÙŠ Ø£Ù† Ø£Ø®Ø·Ø§Ø¡ Ù†Ø·Ù‚ Ø§Ù„ØØ±ÙˆÙ Ø§Ø§Ù„Ù‡Ø¬Ø§Ø¦ÙŠØ© ÙÙŠ Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ù„Ø·Ù„Ø§Ø¨ Ù…Ø¹Ù‡Ø¯ Ø³ÙŠÙ…Ø§Ø·Ø±ÙƒÙŠØ³ Ø¨Ø¨Ø§Ø³Ø§Ù…Ø§Ù† Ø§Ù„Ø´Ø±Ù‚ÙŠØ© Ù„Ù„Ù…Ø±ØÙ„Ø© Ø§Ù„Ø§Ø¨ØªØ¯Ø§Ø¦ÙŠØ© ÙˆØ¬Ø¯Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø¹Ø´Ø±ÙŠÙ† ØØ±ÙÙ‹Ø§ Ù…Ù† Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„Ù†Ø·Ù‚ ÙˆÙ…Ù†Ù‡ Ù†Ø·Ù‚ ØØ±Ù Ø§Ù„Ù‡Ø§Ø¡ ÙˆØ§Ù„Ø¹ÙŠÙ† ÙˆØ§Ù„ØØ§Ø¡ ÙˆØ§Ù„ØºÙŠÙ† ÙˆØ§Ù„Ø®Ø§Ø¡ ÙˆØ§Ù„ÙƒØ§Ù ÙˆØ§Ù„Ù‚Ø§Ù ÙˆØ§Ù„Ø¶Ø§Ø¯ ÙˆØ§Ù„Ø¬ÙŠÙ… ÙˆØ§Ù„Ø´ÙŠÙ† ÙˆØ§Ù„Ø±Ø§Ø¡ ÙˆØ§Ù„Ø·Ø§Ø¡ ÙˆØ§Ù„Ø¯Ø§Ù„ ÙˆØ§Ù„ØªØ§Ø¡ ÙˆØ§Ù„ØµØ§Ø¯ ÙˆØ§Ù„Ø²Ø§ÙŠ ÙˆØ§Ù„Ø¸Ø§Ø¡ ÙˆØ§Ù„Ø°Ø§Ù„ ÙˆØ§Ù„Ø«Ø§Ø¡ ÙˆØ§Ù„ÙØ§Ø¡. Ù…Ù† Ø£Ø³Ø¨Ø§Ø¨ Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ ÙÙŠ ØªÙ„ÙØ¸ Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ù‡Ø¬Ø§Ø¦ÙŠØ© Ø£Ù† Ù…Ù‡Ø§Ø±Ø© Ù‚Ø±Ø§Ø¡Ø© Ø·Ù„Ø§Ø¨ Ù…Ø¹Ù‡Ø¯ Ø³ÙŠÙ…Ø§Ø·Ø±ÙƒÙŠØ³ Ø¨Ø¨Ø§Ø³Ø§Ù…Ø§Ù† Ø§Ù„Ø´Ø±Ù‚ÙŠØ© Ø§Ù„Ù„Ù…Ø±ØÙ„Ø© Ø§Ù„Ø§Ø¨ØªØ¯Ø§Ø¦ÙŠØ© Ø£Ø®Ø·Ø§Ø¡ Ù„ØºÙˆÙŠÙ‹Ø© ÙˆØºÙŠØ± Ù„ØºÙˆÙŠØ©.Â